Further Studies into the Growth of Small Naturally Occurring Three-Dimensional Cracks in Additively Manufactured and Conventionally Built Materials - Shareen Chan; Daren Peng; Andrew S. M. Ang; Michael B. Nicholas; Victor K. Champagne; Aron Birt; Alex Michelson; Sean Langan; Jarrod Watts; Rhys Jones (Crystals, 2025)
MIL-STD-1530D and the United States Air Force (USAF) Structures Bulletin EZ-SB-19-01 require an ability to predict the growth of naturally occurring three-dimensional cracks with crack depths equal to what they term an equivalent initial damage size (EIDS) of 0.254 mm. This requirement holds for both additively manufactured and conventionally built parts. The authors have previously presented examples of how to perform such predictions for additively manufactured (AM) Ti-6Al-4V; wire arc additively manufactured (WAAM) 18Ni 250 Maraging steel; and Boeing Space, Intelligence and Weapon Systems laser bed powder fusion (LPBF) Scalmalloy®, which is an additively manufactured Aluminium-Scandium-Mg alloy, using the Hartman-Schijve crack growth equation. In these studies, the constants used were as determined from ASTM E647 standard tests on long cracks, and the fatigue threshold term in the Hartman-Schijve equation was set to a small value (namely, 0.1 MPa √m). This paper illustrates how this approach can also be used to predict the growth of naturally occurring three-dimensional cracks in WAAM CP-Ti (commercially pure titanium) specimens built by Solvus Global as well as in WAAM-built Inconel 718. As in the prior studies mentioned above, the constants used in this analysis were taken from prior studies into the growth of long cracks in conventionally manufactured CP-Ti and in AM Inconel 718, and the fatigue threshold term in these analyses was set to 0.1 MPa √m. These studies are complemented via a prediction of the growth of naturally occurring three-dimensional cracks in conventionally built M300 steel.